Geochemical characteristics and petrogenesis of four Palaeoproterozoic mafic dike swarms and associated large igneous provinces from the eastern Dharwar craton, India - Srivastava, Rajesh K.; Samal, Amiya K.; Gautam, Gulab C. (Taylor & Francis, 2014)
Palaeoproterozoic mafic dike swarms of different ages are well exposed in the eastern Dharwar craton of India. Available U-Pb mineral ages on these dikes indicate four discrete episodes, viz. (1) ~2.37 Ga Bangalore swarm, (2) ~2.21 Ga Kunigal swarm, (3) ~2.18 Ga Mahbubnagar swarm, and (4) ~1.89 Ga Bastar-Dharwar swarm. These are mostly sub-alkaline tholeiitic suites, with ~1.89 Ga samples having a slightly higher concentration of high-field strength elements than other swarms with a similar MgO contents. Mg number (Mg#) in the four swarms suggest that the two older swarms were derived from primary mantle melts, whereas the two younger swarms were derived from slightly evolved mantle melt. Trace element petrogenetic models suggest that magmas of the ~2.37 Ga swarm were generated within the spinel stability field by ~15–20% melting of a depleted mantle source, whereas magmas of the other three swarms may have been generated within the garnet stability field with percentage of melting lowering from the ~2.21 Ga swarm (~25%), ~2.18 Ga swarm (~15–20%), to ~1.89 Ga swarm (~10–12%). These observations indicate that the melting depth increased with time for mafic dike magmas. Large igneous province (LIP) records of the eastern Dharwar craton are compared to those of similar mafic events observed from other shield areas. The Dharwar and the North Atlantic cratons were probably together at ~2.37 Ga, although such an episode is not found in any other craton. The ~2.21 Ga mafic magmatic event is reported from the Dharwar, Superior, North Atlantic, and Slave cratons, suggesting the presence of a supercontinent, ‘Superia’. It is difficult to find any match for the ~2.18 Ga mafic dikes of the eastern Dharwar craton, except in the Superior Province. The ~1.88–1.90 Ga mafic magmatic event is reported from many different blocks, and therefore may not be very useful for supercontinent reconstructions.